1987
DOI: 10.1021/ie00071a019
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer accompanied by first-order chemical reaction for turbulent duct flow

Abstract: A large-Schmidt-number asymptotic approximation procedure is employed to derive an equation which represents mass transfer accompanied by a first-order chemical reaction for liquids in fully developed turbulent flow in a circular tube. However, since the concentration boundary layer is very thin, the results obtained should also apply to the parallel-plate and concentric-annulus geometries when proper scaling is employed. A modified Van Driest formula for the eddy diffusivity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Their predicted values of the enhancement ratio ζ increased with L / b , and the fully developed values, which ranged up to 9.87 for = 50 and Sc = 50 000, were correlated closely by the expressions and Here = t 1/2 τ w /μ and t 1/2 is the half-life for the reaction. Considering the differences in the modeling, the predicted values of ζ by Hanna et al, when plotted as ζ versus kt 1/2 , were found to agree remarkably well with the essentially exact values of Mitrovic and Papavassiliou. Equation 70 is presumed to be applicable for heat transfer with uniform heating at the wall and an endothermic reaction or the converse if the residence time required for the difference between the wall and mixed-mean temperature to attain half of its value at the inlet is taken as the half-life.…”
Section: Energetic Effectsmentioning
confidence: 67%
See 1 more Smart Citation
“…Their predicted values of the enhancement ratio ζ increased with L / b , and the fully developed values, which ranged up to 9.87 for = 50 and Sc = 50 000, were correlated closely by the expressions and Here = t 1/2 τ w /μ and t 1/2 is the half-life for the reaction. Considering the differences in the modeling, the predicted values of ζ by Hanna et al, when plotted as ζ versus kt 1/2 , were found to agree remarkably well with the essentially exact values of Mitrovic and Papavassiliou. Equation 70 is presumed to be applicable for heat transfer with uniform heating at the wall and an endothermic reaction or the converse if the residence time required for the difference between the wall and mixed-mean temperature to attain half of its value at the inlet is taken as the half-life.…”
Section: Energetic Effectsmentioning
confidence: 67%
“…Hanna et al utilized an eddy diffusivity model of reasonable validity, postulated the analogy between heat and mass transfer, and made a number of numerically justified idealizations to derive an implicit algebraic solution for the enhancement of mass transfer by a first-order irreversible isothermal chemical reaction in the asymptotic limit of large Sc as a function of a + Sc 1/3 and ( k μ/ τ w ) Sc 1/3 only. Their expression predicts enhancements by as high as a factor of 4.…”
Section: Energetic Effectsmentioning
confidence: 99%
“…Hanna et al [7] employed a large Schmidt number asymptotic approximation procedure to derive an analytical solution for the mass transfer from the wall accompanied by a first-order chemical reaction for liquids in fully developed turbulent flow in a circular tube. Meyerink and Friedlander [8] and Harriott and Halmilton [9] have conducted experiments to measure the mass transfer rate of benzoic acid, which dissolved from the wall of a pipe into water or glycerine-water solution in fully developed turbulent flow.…”
Section: Introductionmentioning
confidence: 99%